PENGARUH FAKTOR SOSIODEMOGRAFI DAN LINGKUNGAN TERHADAP KEPADATAN POPULASI LARVA NYAMUK Aedes aegypti DI DESA BENCULUK, KABUPATEN BANYUWANGI - Dian Prima Agustina; Dwi Wahyuni; Slamet Hariyadi (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2016)
Aedes aegypti mosquito which is the main vector of the disease Dengue Hemorrhagic Fever (DHF) and Yellow Fever / Chikungunya. As a result of transovarial transmission of dengue virus within the body of the female mosquito Aedes aegypti into the eggs. The eggs hatch into larvae when already having dengue virus in his body without having to suck the blood of patients with DHF. Population density of Aedes aegypti larvae measured by the density and number of containers is very real impact on cases of dengue transmission. Two factors related to the presence and density of larvae itself include sociodemographic and environmental factors, both of which interact with each other. This study aims to determine the influence of sociodemographic and environmental factors on the population density of Aedes aegypti mosquito larvae in the Village Benculuk and to know the dominant factor causing population density of Aedes aegypti mosquito larvae. The design of the study design using qualitative methods. The results of the study showed the influence of the level of knowledge and behavior with the density of mosquito larvae of Aedes aegypti in the Village Benculuk, Banyuwangi. The influence of the distance between houses, the presence of water reservoirs and fish-eating larvae of the Aedes aegypti mosquito larvae density in the Village Benculuk, Banyuwangi. Environmental factors that affect population density dominates the mosquito Aedes aegypti larvae in the Village Benculuk, Banyuwangi. Keywords: sociodemographic, environmental, and Aedes aegypti.